HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI DENGAN KEPATUHAN IBU MEMBAWA BALITA IMUNISASI DI DUSUN V KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN - Oktafiana Manurung (Excellent Midwifery Journal, 2022)
Background : Immunization is a government program that is required for all children under five, especially basic immunization that aims to improve the National health degree. Providing immunization injections to babies on time is a very important factor for infant health.Goals : This study aims to determine the level of knowledge, compliance, and the relationship between knowledge with maternal obedience to bring toddlers immunization.Methods : The research design used in this research is descriptive correlation by using total sampling in sampling. The number of samples in this study were 40 respondents. The measuring tool used is questionnaire and medical record of subdistrict health center of Tanah Jawa Data analysis techniques used are Chi square, presentation of data in the form of tables and diagrams.Result : The results showed that 45% of respondents had less knowledge and did not adhere to the implementation of immunization 88.9%. Based on Chi square test results showed that there is a statistically significant relationship between knowledge and obedience of mothers to immunization with p value 0.004 <0.05.Conclution : From the research results can be concluded that the lower the mother's knowledge of immunization then the number of non-compliance to immunization will increase. It is recommended to the local health officials to improve health education on the importance of immunization for infants. Keywords: Knowledge, Compliance and Immunization